The Effects of Progressive Muscle Relaxation on Preoperative Anxiety and Blood Pressure in Patient with Aneurysm - Uysal, Dilek; SUKUT, Özge; Demirgil, Bülent Timur (Nursing and Health Sciences Journal (NHSJ), 2023)
This study, conducted on diagnosed aneurysm patients, in order to test the effects of progressive muscle relaxation on blood pressure and anxiety levels in the preoperative period, was carried out in a quasi-experimental study with a pre-test and post-test application. The data of this study were collected between January 2022-September 2022 at the neurosurgery clinic on 38 patients (twenty women and eighteen men) who’ve been diagnosed with cerebral aneurysm, awaiting a surgical operation, and have other criteria to be taken into the study. Pre- and post-exercise vital signs and anxiety levels of patients receiving progressive muscle relaxation exercises for twenty minutes in the preoperative period were measured with the Visual Analogue Scale (VAS) and Beck Anxiety Inventory (BAI). Frequency analysis for descriptive statistics, and t-test analysis for blood pressure, pulse, respiration, BAI, and VAS scores in a single group were utilized. Progressive muscle relaxation exercises in the preoperative period for neurosurgery patients diagnosed with aneurysm have statistically significant effects in reducing the patients’ anxiety and blood pressure (p<0.001). It is recommended that progressive muscle relaxation exercises be used in the clinic during the preoperative period. A clinically important finding is the positive effect of progressive muscle relaxation exercises on patients' vital signs and anxiety.